PRESERVATION OF COTTON FISH NET TWINES BY TANNING II. FIXATION OF TANNIN - CECILY, P J; KUNJAPPAN, M K (Fishery Technology, 2016)
Fix~tiv~ beha~iour of tannin belonging to three functional groupswas stud1ed m deta1l using copper sulphate and potassium dichromateas oxidising agents.